Subverting civilian control: security sector reform and autocratisation in Turkey (2002–2017) - Sentek, Zeynep (2020)
This thesis aims to explain why the acclaimed civilianisation project of the AKP government did not achieve meaningful democratisation in Turkey. The key question of this research is as follows: Why did democratisation not follow political demilitarisation under AKP rule in Turkey and why have the civil-military reforms contributed to autocratisation and the emergence of a competitive authoritarian setup? The thesis will answer these questions through building up one main and two auxiliary causal mechanisms covering the full period from the takeover of the government by the AKP in 2002 until the end of 2017. At the end, it aims to reveal a process of political demilitarisation that turned into autocratisation where a new coercive structure has been forged, together with the rebuilding of the socio-political domain in the form of securitisation of dissent, and the rebuilding of the economic domain in the form of securitisation of wealth.